PELATIHAN SAPTA PESONA KENANGAN DI PULAU BULUH KECAMATAN BULANG KOTA BATAM - Nensi Lapotulo; Kiki Widia; Aisah (PUSLITABMAS-Politeknik Pariwisata Batamc, 2023)
This community service aims practicing and making the handicraft products that were produced to increase household income and also participate in developing their own regional tourism potential by making something or souvenirs that are characteristic of their region. The Sapta Pesona’s training was attended by the people of Buluh Island, both men and women, consisting of housewives, businesspeople and other people who have an interest in souvenirs. The training is carried out by providing education and outreach about one form of Sapta Pesona, namely Kenangan in the form of souvenirs which are then followed by exploration and practice of making handicrafts or souvenirs. The resulting output is that the trainees have additional expertise and are expected to start practicing and producing through creative industries which are currently increasingly advanced because they can be applied in various sectors one of which is tourism, which in turn can improve the people's economy, especially for the Buluh Island